Study of the factors influencing the choice of scaffolds for the implementation of the strengthening processes of building structures during reconstruction - Tonkacheiev, H.; Rudnieva, I. (Ways to Improve Construction Efficiency, 2021)
The article clarifies the influence of the technical condition of the structure, as well as the structural, technological and organizational parameters that determine the organizational and technological scheme for the production of construction works for reconstruction, as major factors affecting the choice of scaffolds for the implementation of strengthening processes of building structures. The choice of scaffolds for the implementation of the processes of strengthening building structures during reconstruction is a complex organizational and technological process that requires analysis, preparation and verification of decisions. Reconstruction works should be carried out in a short time with a combination of two technologies in site (industrial, production, and construction). During the repair and reconstruction of existing workshops, a large volume of assembly and repair operations during the replacement and reinforcement of building structures is carried out inside the building at a considerable height. Labor costs for the arrangement of the scaffold often exceed the labor costs for the main work that are performed using these funds, which in turn affects the cost of the reconstruction project and the time it takes to complete the work. In these conditions, the labor intensity of construction and installation works sharply increases. Therefore, for the conditions of reconstruction, it is necessary to investigate the regularities of the choice of scaffolds for the implementation of the processes of strengthening building structures, depending on a number of factors. In order to study the features and properties of the scaffolds, a set of influencing factors was found and the final indicators for scaffolds types were studied. They are obtained from the analysis of the structural, technological and organizational parameters of the scaffold. of the whole set of factors, the most important and complex subgroup is the type of equipment and equipment layout in workshops. For their selection and analysis, objects of mechanical engineering and metallurgy were considered, taking into account the nature and severity of products, the nature of the technological process and the size of the shops. Further, according to the nomenclature of existing scaffolds, those parameters and factors should be selected that can be used when strengthening and replacing the corresponding building structures.